Immunophenotype and function define TCRγδ + T-ALL as a distinct subgroup from TCRαβ + T-ALL patients. Issue 1 (2nd January 2020) - Mirji, Gauri; Banavali, Shripad; Sengar, Manju; Chiplunkar, Shubhada V.
Abstract: We recently demonstrated TCRγδ + T-ALL as a distinct subgroup from TCRαβ + T-ALL at genomic level. TCRγδ + T-ALL subgroup possess significant survival advantage compared to TCRαβ + T-ALL. In the present study, functional level differences in these two subgroups of T-ALL were studied to understand the immune scenario contributing to survival benefit of TCRγδ + T-ALL subgroup. TCRγδ clonal T-ALL patients showed significantly high levels of γδ T cells compared to TCRαβ clonal T-ALL patients. TCRγδ + T-ALL patients expressed significantly high central memory and terminally differentiated (TemRA) Vδ1 and Vδ2 T cells. TCR γδ clonal leukemic blasts stimulated increased number of Vδ2 T cells from healthy lymphocytes. TCR γδ clonal leukemic blasts were able to form efficient immune synapse with effector γδ T cells. The differences in immunophenotype, cytotoxicity and immune synapse formations corroborate TCRγδ + T-ALL as a distinct subgroup from TCRαβ + T-ALL patients and explain the survival benefit of TCRγδ + T-ALL patients.